2018
DOI: 10.3389/fmicb.2018.00262
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Membrane-Derived Vesicles Promote Bacterial Virulence and Confer Protective Immunity in Murine Infection Models

Abstract: Staphylococcus aureus produces membrane-derived vesicles (MVs), which share functional properties to outer membrane vesicles. Atomic force microscopy revealed that S. aureus-derived MVs are associated with the bacterial surface or released into the surrounding environment depending on bacterial growth conditions. By using a comparative proteomic approach, a total of 131 and 617 proteins were identified in MVs isolated from S. aureus grown in Luria-Bertani and brain-heart infusion broth, respectively. Purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 73 publications
5
68
1
Order By: Relevance
“…The lower degree of protection we observed for MMC-induced CMVs than for FLU-induced CMVs in the bacterial protection assay could be due to the fact that CMVs induced by SOS response activation carry phage endolysins that can affect cell viability (4,25,26). Askarian et al recently showed that CMVs naturally produced by S. aureus protect cells from whole-blood killing (12). We observed a similar effect for CMVs produced by S. aureus in response to DNA damage or antibiotic stress, suggesting that the mechanism of CMV genesis does not affect the protective function of CMVs against the host innate immune defense (12).…”
Section: Figmentioning
confidence: 73%
See 2 more Smart Citations
“…The lower degree of protection we observed for MMC-induced CMVs than for FLU-induced CMVs in the bacterial protection assay could be due to the fact that CMVs induced by SOS response activation carry phage endolysins that can affect cell viability (4,25,26). Askarian et al recently showed that CMVs naturally produced by S. aureus protect cells from whole-blood killing (12). We observed a similar effect for CMVs produced by S. aureus in response to DNA damage or antibiotic stress, suggesting that the mechanism of CMV genesis does not affect the protective function of CMVs against the host innate immune defense (12).…”
Section: Figmentioning
confidence: 73%
“…Askarian et al recently showed that CMVs naturally produced by S. aureus protect cells from whole-blood killing (12). We observed a similar effect for CMVs produced by S. aureus in response to DNA damage or antibiotic stress, suggesting that the mechanism of CMV genesis does not affect the protective function of CMVs against the host innate immune defense (12). Since phage binding to the surface of strain CI1449 is impaired, the presence of phages in MMC-induced CMV preparations is not responsible for the protective effect observed against killing by DAP and whole blood.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane vesicles (MVS) were isolated from a commensal S. haemolyticus strain (57-1), and a clinical S.haemolyticus strain (51-08), according to the methods described in [1], [4]. Briefly, proteins secreted into the bacterial growth medium was harvested after the culture was centrifuged and filtered through a 0.22 µm polyethersulfone membrane (Millipore express plus, Merck Millipore, Burlington, USA).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…OMVs can be considered having various roles in pathogenesis of bacteria, such as mediators of information exchange between bacteria and host [4] and vehicles of virulence factor transport [5]. Besides that, a recent study shows that bacterial OMVs have immunomodulatory activities, which make OMVs potential vaccine candidates for bacterial infection therapy and provide enlightened strategies for the development of antibacterial technologies [6][7][8]. Although there are amounts of evidences indicating that OMVs can trigger potent innate immune response in host cell and protect the host against bacterial infection [9,10], the exact mechanisms involved in the immune response induced by OMVs remain uncertain.…”
Section: Introductionmentioning
confidence: 99%